2013
DOI: 10.1186/1756-3305-6-276
|View full text |Cite
|
Sign up to set email alerts
|

The ovarian transcriptome of the cattle tick, Rhipicephalus (Boophilus) microplus, feeding upon a bovine host infected with Babesia bovis

Abstract: BackgroundCattle babesiosis is a tick-borne disease of cattle with the most severe form of the disease caused by the apicomplexan, Babesia bovis. Babesiosis is transmitted to cattle through the bite of infected cattle ticks of the genus Rhipicephalus. The most prevalent species is Rhipicephalus (Boophilus) microplus, which is distributed throughout the tropical and subtropical countries of the world. The transmission of B. bovis is transovarian and a previous study of the R. microplus ovarian proteome identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Genes involved in immunity, stress, and defense responses showed up-regulation in response to B. bovis infection (Heekin et al, 2012), while genes encoding for calreticulin, kunitz-type serine protease inhibitors and microplusin which exhibits antimicrobial activity, were differentially expressed in B. bovis/B. bigemina infected Rhipicephalus ticks (Rachinsky et al, 2007; Antunes et al, 2012; Heekin et al, 2013; Lu et al, 2016). Tick SUB (Almazán et al, 2005) was shown to be up-regulated in B. microti inoculated intrahemocoelically into Rhipicephalus haemaphysaloides (Lu et al, 2016) and B. bigemina -infected R. microplus (Merino et al, 2013) (Figure 2D).…”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 99%
“…Genes involved in immunity, stress, and defense responses showed up-regulation in response to B. bovis infection (Heekin et al, 2012), while genes encoding for calreticulin, kunitz-type serine protease inhibitors and microplusin which exhibits antimicrobial activity, were differentially expressed in B. bovis/B. bigemina infected Rhipicephalus ticks (Rachinsky et al, 2007; Antunes et al, 2012; Heekin et al, 2013; Lu et al, 2016). Tick SUB (Almazán et al, 2005) was shown to be up-regulated in B. microti inoculated intrahemocoelically into Rhipicephalus haemaphysaloides (Lu et al, 2016) and B. bigemina -infected R. microplus (Merino et al, 2013) (Figure 2D).…”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 99%
“…Transcriptomes from the R. microplus gut (Heekin et al, 2013a), ovaries (Heekin et al, 2013b), and synganglion (Guerrero et al, 2016) were previously described. The transcriptome from the fore leg (Haller's organ) (4888 sequences) was obtained by similar methods to those described in Guerrero et al (2016).…”
Section: Organ-specific Transcriptomes From Rhipicephalus Microplusmentioning
confidence: 99%
“…The sialotranscriptome of A. variegatum (36), A. americanum (37)(38)(39), D. variabilis (39), I. scapularis (40,41), I. ricinus (42), D. andersoni Alarcon-Chaidez; (43) and R. appendiculatus (44) have been determined. R. microplus transcriptomes of larvae (45)(46)(47)(48)(49), engorged female gut (50), ovary (51), and synganglia (52) have been reported recently. The full-length coding sequences of numerous proteins and unique protein tick protein families have been described based in these analyses and their roles during host-parasite interaction described.…”
Section: Omics Approaches In Tick Vaccine Developmentmentioning
confidence: 98%